Adolescents' ability to select healthy food using two different front-of-pack food labels: a cross-over study. Issue 6 (17th May 2013) - Babio, Nancy; Vicent, Paloma; López, Leonor; Benito, Anna; Basulto, Julio; Salas-Salvadó, Jordi
Abstract Objective To compare, in adolescents, two models of front-of-pack Guideline Daily Amounts (GDA) labels in terms of (i) friendliness and acceptance and (ii) the ability to choose a diet that closely follows the nutritional recommendations. Design A randomized cross-over study was designed to compare two simplified front-of-pack GDA nutrition labels. Setting A Spanish secondary school. Subjects Eighty-one healthy adolescents aged between 14 and 16 years were recruited. Participants were randomly exposed to two experimental non-real food-choice conditions using multiple-traffic-light or monochrome nutritional labels. Participants had to choose options from a closed menu for 5 d on the basis of the experimental front-of-pack labelling. For each meal, three food options with different nutritional compositions were given to the participants. The contents of total energy and fat, saturated fat, sugar and salt of the chosen options were calculated. Results There were no significant differences in baseline sociodemographic and anthropometric characteristics between participants regardless of the experimental condition in which they started. There were no carry-over effects between the experimental sequences. It was observed that when participants used the multiple-traffic-light GDA system they chose significantly less total energy (mean –123·1 (sd 211·0) kJ (−29·4 (sd 50·4) kcal), P < 0·001), sugar (−4·5 (sd 4·6) g, P < 0·001), fat (−2·1 (sd 4·5) g, P = 0·006), saturated fat (−1·0 (sd 1·9) g, P = 0·002) and salt (−0·4 (sd 0·5) g, P < 0·001) than when they used the monochrome GDA system. Conclusions Compared with the monochrome GDA front-of-pack nutritional label, the multiple-traffic-light system helped adolescents to differentiate between healthier and less healthy food, theoretically making it possible for them to choose a diet closer to dietary recommendations.